Poesia em Língua de Sinais Americana (ASL) : um estudo semiótico com alunos universitários surdos brasileiros - Silva, Mariane Linhares da (2025)
This study aimed to investigate the aesthetic elements present in literary works created by Deaf authors in American Sign Language (ASL). To carry out this project, the theoretical framework was based on Sutton-Spence (2021) and Peixoto (2023). The main objective was to examine how Brazilian Deaf university students comprehend the content of poems in ASL. Derived from this main goal, the following specific objectives were established: (1) to analyze how Brazilian Deaf individuals receive poetic texts in ASL; (2) to identify, in the students’ responses, which aesthetic elements of Deaf literature used by American poets most contributed to their comprehension of the works; and (3) to contribute to the dissemination of knowledge about the aesthetic and literary language of sign language. To achieve these goals, the study was structured into three practical stages: a semi-structured interview, a training minicourse on Deaf literature aesthetics, and the reapplication of the same semi-structured interview after the minicourse. This research adopted an action-research design, and the methodological approach used for data analysis was qualitative, following Ludke and André (1986). The data collection instrument consisted of documentary analysis of video recordings containing the Deaf students’ responses. At the end of the study—particularly after participating in the minicourse—the Deaf university students showed significant improvement in understanding the aesthetic language of the ASL poems that comprised the research corpus: The Rosebush by Ella Mae Lentz, Caterpillar by Ian Sanborn, and A Creative Storytelling Without Words by Douglas Ridloff. The findings revealed that the visual-spatial modality of sign language contributes to Deaf individuals’ linguistic comfort, enabling them to access Deaf literature while fostering the exchange of knowledge and experiences. It was also observed that Deaf culture, language, and identity were shared among participants, creating a collective space for learning and reflection. This research proved relevant not only for understanding Deaf literature but also for valuing Deaf culture and identity, promoting dialogue among diverse life experiences and perspectives.